2023
DOI: 10.1038/s41598-023-28875-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reproducibility and up-scaling of the synthesis of Er,Yb-doped NaYF4-based upconverting nanoparticles and control of size, morphology, and optical properties

Abstract: Lanthanide-based, spectrally shifting, and multi-color luminescent upconverting nanoparticles (UCNPs) have received much attention in the last decades because of their applicability as reporter for bioimaging, super-resolution microscopy, and sensing as well as barcoding and anti-counterfeiting tags. A prerequisite for the broad application of UCNPs in areas such as sensing and encoding are simple, robust, and easily upscalable synthesis protocols that yield large quantities of UCNPs with sizes of 20 nm or mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…With the progression of epitaxial growth, a disk-shaped morphology eventually forms when more OA ligands are chosen to bond to the (001) facet. Interestingly, our results align with some aspects of the research conducted by Markus Haase, Ute Resch-Gengern, and Paul Alivisatos. ,, …”
Section: Resultssupporting
confidence: 91%
“…With the progression of epitaxial growth, a disk-shaped morphology eventually forms when more OA ligands are chosen to bond to the (001) facet. Interestingly, our results align with some aspects of the research conducted by Markus Haase, Ute Resch-Gengern, and Paul Alivisatos. ,, …”
Section: Resultssupporting
confidence: 91%
“…The maximum slope was obtained by converting the values of Δ to T and the values of steps to micrometers. For this derivative, D x = 1.0(3) K μm −1 was calculated, which can be fed into eq 4 to estimate the spatial resolution obtaining σ X = 0.24 (7) μm, in close agreement with previously reported values. 44 A word of caution is needed here.…”
Section: Andsupporting
confidence: 86%
“…It was possible to resolve the thermal gradients produced by the Joule effect on the scale of microns. From temperature line profiles, it was possible to calculate the spatial resolution of the setup: σ X = 0.24 (7) μm. Similarly, the temperature resolution σ T = 0.24(2) K was obtained using the m-UCNPs that presented the highest thermal sensitivity 1.741 (% K −1 ) at 300 K. Given that all resolutions are strongly dependent on the relative sensitivity of the UCNPs used, efforts in the design and synthesis of highly sensitive particles are a key factor to improve the technique.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 nm luminescent UCNPs with 57% Yb encouraged us to carry out this strategy. As it has been reported that substantial variability in the average UCNP diameter could be observed for a defined synthetic protocol, 55,56 we simply repeated the abovementioned synthesis of Na(Yb57%-Gd42%)F4:Tm1%. While the PSD remained constant owing to our new heating method, we could achieve the preparation of ultrasmall UCNPs ranging from 3.86 nm down to 2.84 nm in diameter, the target size for single-Tm-ion UCNPs (Fig.…”
Section: Figurementioning
confidence: 99%